SOCIO-ECONOMIC ADVANTAGES OF A GRADUAL INCREASE IN THE RETIREMENT AGE IN UZBEKISTAN BASED ON THE EXPERIENCE OF THE EUROPEAN PENSION SYSTEM - Abdullayayeva Madinaboni Khasanboyevna (Ecominds Press, 2025)
This article thoroughly examines the socio-economic advantages associated with gradually increasing the retirement age in Uzbekistan by drawing insights from European pension reform experiences. It highlights key aspects such as pension sustainability, labor market engagement, demographic shifts, and economic stability. Detailed recommendations are proposed for Uzbekistan to effectively implement these practices, ensuring socio-economic resilience and pension fund sustainability.
Keywords: Retirement age, pension reform, socio-economic benefits, labor market dynamics, demographic trends, Uzbekistan, Europe, pension sustainability, economic stability.